O patrimônio vivencial no intercâmbio virtual: proposta de mobilidade na internacionalização do Ensino Superior Tecnológico - Lopes, José Carlos Barbosa (2023)
This research aimed to investigate, propose and analyze activities that mobilize funds of perejivanie from the experience of Higher Technological Education students, in a public institution in the state of São Paulo, involved in a virtual exchange program in English based on Engaged Multiliteracy. The research deals with the activities carried out by Brazilian and North American students with a focus on the formation and expansion of students’ funds of perejivanie (MEGALE; LIBERALI, 2020), a concept that encompasses a range of resources that individuals gather through dramatic events (VYGOTSKY, 1934/1994). This research emphasized the experiences lived in multiple space-time dimensions as potential for the development of human mobility (BLOMMAERT; BACKUS, 2011, 2012) due to the interdependence of affective and cognitive processes (LIBERALI; FUGA, 2018) accessed in the various spheres and trajectories of social life. In the case of English teaching-learning situations, the pedagogical proposal of Engaged Multiliteracy (LIBERALI, 2022) promoted engagement and social transformation (FREIRE, 1970/2005) while it shows evidence of how participants valued their funds of perejivanie in the different forms of expression and action in the virtual exchange experience. In Higher Technological Education, this research investigated the implications in the curriculum, considering the virtual exchange proposal as one of the institution's internationalization initiatives (MENDES; FINARDI, 2023; FINARDI, 2019). Grounded in Applied Linguistics studies, the methodological approaches were based on the Collaborative Critical Research (MAGALHÃES, 2006f, 2014), which implies the negotiation of meanings among participants involved in different activities (LEONTIEV, 1972). Data interpretation and discussion resorted to enunciative, discursive and multimodal categories in educational contexts (LIBERALI, 2013, 2018). This framework sought to elucidate intercultural (CANDAU, 2012, 2020) and decolonial (WALSH, 2010, 2012) practices that legitimize the ecology of knowledges in a world undergoing post-pandemic transition (SANTOS, 2021). The results addressed alternatives to internationalization through a critical and creative perspective towards language practices aligned with the other resources in the funds of perejivanie to transform realities